Dosimetric impact of air pockets in the vaginal cuff brachytherapy using model-based dose calculation algorithm - Lakshmi Venkataramana Puriparthi; Anil Kumar Talluri; Naga Prasanthi Akkineni; Harjot Kaur Bajwa; Venkatappa Rao Tumu; N V. N Madhusudhana Sresty; Krishnam Raju Alluri (Journal of Medical Physics, 2023)
Background: Endometrial cancer is the most common disease of the female reproductive system. Vaginal cuff brachytherapy (VCB) has intrinsic advantages compared to external beam therapy when treated with radiation. A single-channel cylinder is a standard applicator in VCB. The present study aims to estimate a change in the dose to vaginal mucosa due to air pockets between the cylinder and vaginal mucosa by calculating with the Acuros BV algorithm and comparing it to the Task Group 43 (TG-43) algorithm. Materials and Methods: Patients who presented with air packets were included retrospectively. For each patient, three plans were created: the first plan used TG-43, the second plan used dose recalculation with Acuros BV, and the third plan was generated by re-optimization by Acuros BV. On the same axial computed tomography image, the point doses at the cylinder's surface and the displaced mucosa were recorded and the ratios were then estimated. Results: The average volume of air pockets was 0.08 cc (range of 0.01–0.3 cc), and 84% of air pockets displaced the vaginal mucosa by ≥0.2 cm. The average ratios of dose were 0.77 ± 0.09 (1 standard deviation [SD]) and 0.78 ± 0.09 (1 SD) for TG-43 and Acuros BV algorithms, respectively. Due to the air pocket, mucosa received a reduced dose by an average of 22.72% and an average of 23.29% for TG-43 and Acuros BV, respectively. The maximum displacement of mucosa and the ratio of doses were negatively correlated for both. In the Optimized Acuros BV plan, total dwell time increased by 1.8% but no considerable change in the dose ratios. Conclusion: The calculated dose of mucous membrane forced out of the cylinder surface by air pockets by the Acuros BV algorithm was nonsignificantly different from TG-43. Therefore, even in the presence of air pockets, the TG-43 algorithm for calculating the VCB dose is appropriate.